2019
DOI: 10.1016/j.tranon.2018.10.010
|View full text |Cite|
|
Sign up to set email alerts
|

High Keratin 8/18 Ratio Predicts Aggressive Hepatocellular Cancer Phenotype

Abstract: BACKGROUND & AIMS: Steatohepatitis (SH) and SH-associated hepatocellular carcinoma (HCC) are of considerable clinical significance. SH is morphologically characterized by steatosis, liver cell ballooning, cytoplasmic aggregates termed Mallory-Denk bodies (MDBs), inflammation, and fibrosis at late stage. Disturbance of the keratin cytoskeleton and aggregation of keratins (KRTs) are essential for MDB formation. METHODS: We analyzed livers of aged Krt18−/− mice that spontaneously developed in the majority of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
(75 reference statements)
1
16
0
Order By: Relevance
“…This indicates that analysis of the expression of fibrosis marker genes can be used for monitoring the progression of NAFL to NASH. Similar results of early upregulation fibrosis marker genes, including Col1a1 and Tnf , and a high Krt8/Krt18 ratio were observed in a diet‐induced mouse model of hepatic fibrosis 18 and in a Krt18 −/− transgenic mouse model of NASH 31 …”
Section: Discussionsupporting
confidence: 70%
“…This indicates that analysis of the expression of fibrosis marker genes can be used for monitoring the progression of NAFL to NASH. Similar results of early upregulation fibrosis marker genes, including Col1a1 and Tnf , and a high Krt8/Krt18 ratio were observed in a diet‐induced mouse model of hepatic fibrosis 18 and in a Krt18 −/− transgenic mouse model of NASH 31 …”
Section: Discussionsupporting
confidence: 70%
“…In addition, KRT18 expression had 4.6-times increase in high metastatic lung cancer cell line compared with low metastatic lung cancer cell line [26]. In hepatocellular carcinoma patients, levels of KRT18 expression were positively correlated with lymph node metastasis and aggressive phenotype [27,28]. Moreover, Afrem et al [29] reported KRT18 overexpression was correlated with advanced clinical stage, poor differentiation, and high invasion pattern in oral squamous cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, particular stains such as cytoplasmic keratin (KRT) 8/18 immunohistochemistry may detect ballooned hepatocytes. A recent study by Golob-Schwarzl et al [8] found that a high KRT8/18 ratio caused the change in hepatic lipid profile resulting in ballooning with a Mallory–Denk body (MDB) formation. Numerous risk factors, such as metabolic derangement, obesity, and insulin resistance (IR) lead to liver accumulation of triglycerides and free fatty acids and growing of NAFLD [9].…”
Section: Introductionmentioning
confidence: 99%